STRENGTHENING THE PANCASILA CHARACTER OF ELEMENTARY CHILDREN PREVENTING SEXUAL CRIME FROM SOCIAL MEDIA - Jacobus, Susan N H; Pangalila, Theodorus; Surentu, Olvi Steva; Tampi, Debora (Wahana Sekolah Dasar, 2023)
Abstract: Technological developments in the 4.0 era had a negative influence on the character of students, so that continuous efforts were needed through strengthening the Pancasila character, as a solution to the degradation of student character. The negative influence of technology has led to many cases related to sexual crimes, as a result of social media exposure has become a major threat for elementary school children. This study aims to analyze qualitatively the values of Pancasila which can provide character strengthening for elementary school students to prevent the negative influence of social media, especially cases of sexual crimes. This study uses a qualitative method of literature study. The results of the study show that strengthening the character of Pancasila values, namely the character values of faith, piety to God Almighty and noble character have the potential to prevent sexual crimes originating from social media.